Multimodal opioid-free analgesia in pediatric abdominal surgery: safety and speed of recovery. (Herald of the National Children's Medical Center, 2025)
Background. To evaluate the efficacy, safety, and recovery rate of multimodal non-opioid analgesia (MBA) compared with an opioid regimen in children after abdominal surgery.Materials and methods. A prospective clinical study included 131 patients (5-17 years old) undergoing elective surgery. The IBA group (n=101) received paracetamol and ibuprofen, the comparison group (n=30) -morphine. Pain intensity (Wong-Baker scale), inflammatory biomarkers (IL-6, CRP), side effects, time to extubation and parental satisfaction were evaluated.Results. The IBA group showed: less pain (0.9±1.2 vs. 4.2±2.0, plt;0.001), lower need for additional analgesia (36% vs. 81%, plt;0.001), minimal side effects (nausea 5% vs. 50%), lower IL-6 and CRP (plt;0.01), shorter time to extubation (42±8 vs 66±11 min, plt;0.001) and higher parental satisfaction (9.3±0.5 vs 7.8±1.1, plt;0.01).Conclusion. IBA provides better pain control, lower complication rates, and faster recovery compared with opioids. The method is recommended for wide application in pediatric surgery.
Keywords: multimodal analgesia; children; abdominal surgery; opioid-free approach; paracetamol; ibuprofen; pain; recovery; safety; inflammation